Effectiveness of selection and recruitment process: Beximco Pharmaceuticals Limited(BPL) - Jahan, Tanjila (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.